Pengetahuan Remaja tentang Infeksi Menular Seksual di SMA Negeri 1 Singaraja - Putu Intan Daryaswanti; Priyo Utomo; Ni Made Diah Pusparini Pendet (Jurnal Kesehatan Medika Udayana, 2021)
Background: Sexually Transmitted Infections are diseases that are transmitted through sexual contact. Most of the sufferers of this disease are adolescents aged 15-24 years. The high risk factor for this disease is adolescents because of the usual premarital sexual behavior. Sexuall transmission disease are still a health problem in various countries. One of the reasons is the relatively low level of adolescent knowledge. The purpose of this study was to describe the level of adolescent knowledge about sexually transmitted infections in SMA Negeri 1 Singaraja. Method: This research uses descriptive method with survey approach. The population in this study were teenagers in SMA Negeri 1 Singaraja with a sample of 293 samples. The sampling technique used in this study was simple random sampling. The measuring instrument in this study used a closed questionnaire with 30 questions. The data is then processed using SPSS. The data analysis method in this research is qualitative data analysis method. Results: The results of the 293 respondents, the knowledge of adolescents about sexually transmitted infections were mostly in the good category. Adolescents with a good level of knowledge were 260 respondents (88.7%), 30 respondents (10.2%) in moderate category, and 3 respondents (1.0%) in poor category. Conclusion: The majority of adolescents' knowledge level about sexually transmitted infections in SMA Negeri 1 Singaraja was in the good category as many as 260 respondents (88.7%). The results of this study are expected to be input for adolescents to always pay attention to their health and as an effort to prevent sexually transmitted infections.